2017
DOI: 10.1007/jhep11(2017)028
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling decay of false vortices with gravitation

Abstract: Abstract:We study the effect of vortices on the tunneling decay of a symmetry-breaking false vacuum in three spacetime dimensions with gravity. The scenario considered is one in which the initial state, rather than being the homogeneous false vacuum, contains false vortices. The question addressed is whether, and, if so, under which circumstances, the presence of vortices has a significant catalyzing effect on vacuum decay. After studying the existence and properties of vortices, we study their decay rate thro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…This result is not exclusive to false skyrmions. It was also observed for vortices [34]. This can be understood in the following way.…”
Section: Vacuum Decay Ratesmentioning
confidence: 59%
See 1 more Smart Citation
“…This result is not exclusive to false skyrmions. It was also observed for vortices [34]. This can be understood in the following way.…”
Section: Vacuum Decay Ratesmentioning
confidence: 59%
“…where we maintain the thin-wall approximation for which r ≈ R on the wall. To compute this term, it is useful to introduce the Gaussian normal coordinate system (see [34] for an example of the application in the vortex system)…”
Section: Tunnelling Decaymentioning
confidence: 99%
“…They obtained an analytical expression for the black hole mass 𝑀 in terms of the scalar charge 𝑐 and the winding number 𝑛. Later, how vortices affect the tunneling decay of a symmetry-breaking false vacuum in 2 + 1 dimensional Einstein gravity was studied in [3]. There have also been recent studies of gravitating magnetic monopoles [4].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, they obtain a compact analytical expression for the black hole mass M in terms of the scalar charge c and the winding number n: M = λ 2 c 2 /4+n 2 where λ 2 is a parameter appearing in the potential. More recently, the effect of vortices on the tunneling decay of a symmetry-breaking false vacuum in 2 + 1 dimensional Einstein gravity was studied [6]. They found that the tunneling exponent for vortices, the dominant factor in the decay rate, is half that of Coleman-de Luccia bubbles [7].…”
Section: Introductionmentioning
confidence: 99%